Impact of programming mechanisms on the performance and reliability of nonvolatile memory devices based on Si nanocrystals - Ng, Chi Yung (2010)
A nonvolatile memory based on silicon nanocrystals (nc-Si) synthesized with very-low-energy Si+ implantation is fabricated, and the memory performance under the programming/erasing of either Fowler-Nordheim (FN)/FN or channel hot electron (CHE)/FN at both room temperature and 85°C is investigated. The CHE programming has a larger memory window, a better endurance, and a longer retention time as compared to FN programming. In addition, the CHE programming yields less stress-induced leakage current than FN programming, suggesting that it produces less damage to the gate oxide and the oxide/Si interface. Detailed discussions on the impact of the programming mechanisms are presented.